Population Size Estimation of People Who Inject Drugs: An Overview of Methodologies - Diana M. Tordoff; Adam Palayew; Brittany N. Price; Courtney McKnight; Don Des Jarlais; Elise Healy; Kelly Knudtson; Katelyn Benhoff; Lesly-Marie Buer; Sara Glick; Sarah Deutsch (My University, 2023)
This document provides an overview of the different methods and considerations for estimating the size of the population who injects drugs. It is primarily intended for local health departments, academia, and other community-based organizations.
Keywords: People Who Inject Drugs; Population Estimate